El uso de documentos y escritos en la audiencia de juicio oral - Decastro González, Alejandro (2023)
The coming into effect of the adversarial criminal system in most of Latin America, which occurred during the final years of the previous century and the beginning of the present one, suggests fundamental changes in litigation. One of those changes has to do with the a ppropriate use of documents and writings in the oral trial hearing, an aspect th at was not problematic in the previous mixed-written procedural systems with an inquisitive tendency. The present article approaches that problem and pr oposes the correct use that should be given to documents and writings during the oral trial hearing.